Mackinawite formation from elemental iron and sulfur - Bolney, Robert; Grosch, Mario; Winkler, Mario; van Slageren, Joris; Weigand, Wolfgang; Robl, Christian (RSC advances, 2021)
Sulfur-assisted corrosion is a process known to material scientists for many decades now. Though the corrosion of iron in the presence of sulfur has been studied extensively, it has never been used to intentionally synthesize mackinawite. In contrast to the conventional preparation of mackinawite by precipitation, the synthesis from the elements can be carried out without additional ions. This makes it possible to investigate the influence of any dissolved salts on the mackinawite formation and its properties. We found that the addition of NaCl significantly accelerates the reaction and furthermore influences the Fe 2+ ion content of the formed mackinawite itself. This finding leads us to propose a novel model of charged layers which can be used to explain some of the inconsistencies found in the literature regarding the structure and particle characteristics of nano-mackinawite. Nanoparticulate mackinawite was synthesized from elemental iron and sulfur in a convenient and reliable reaction. The structure and composition of the products were characterized and a new model describing the particle characteristics is established.